Who has the cure? Hamilton Project ideas on health care - Furman, Jason (Brookings Institution Press, 2008)
"Emphasizes the importance of universal health care and looks at alternatives for achieving universal health care coverage that also improves efficiency in the health care industry and provides proposals to improve the effectiveness and affordability of health care, including income-related cost-sharing, expanding preventive care, and reforming Medicare's prescription drug benefit"--Provided by publisher.